2021
DOI: 10.1186/s12882-021-02319-9
|View full text |Cite
|
Sign up to set email alerts
|

Do the patient education program and nurse-led telephone follow-up improve treatment adherence in hemodialysis patients? A randomized controlled trial

Abstract: Background End-Stage Renal Disease (ESRD) is the final and permanent stage of Chronic Kidney Disease (CKD). Hemodialysis (HD) is the most common treatment for CKD. To have desirable therapeutic outcomes, patients have to adhere to a specific therapeutic regimen that reduces the hospitalization rate and side-effects of HD. The present study aimed to determine the effects of the patient education program and nurse-led telephone follow-up on adherence to the treatment in hemodialysis patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 35 publications
2
21
1
3
Order By: Relevance
“…The mean pre-pandemic scores of ESRD-AQ sub-domains in this study were consistent with those reported by Naalweh et al [ 15 ] except for the mean HD attendance and medication adherence scores which were lower than Naalweh's study (268.3 vs. 296.36, and 160.2 vs 184.32, respectively) [ 15 ]. In contrast, our mean scores of the total adherence behavior and its sub-domains were all higher than those reported by Arad et al [ 22 ] which reported a total adherence score of 513.6 compared to 919.8 in our study. Furthermore, non-adherence behaviors among ESRD patients showed wide variations in the literature ranging from 2% to 80.4% for dietary restrictions, 9.7%–75.3% for fluid restrictions, 15.4%–99% for medical prescriptions, and to HD attendance as 33.6%.…”
Section: Discussioncontrasting
confidence: 99%
“…The mean pre-pandemic scores of ESRD-AQ sub-domains in this study were consistent with those reported by Naalweh et al [ 15 ] except for the mean HD attendance and medication adherence scores which were lower than Naalweh's study (268.3 vs. 296.36, and 160.2 vs 184.32, respectively) [ 15 ]. In contrast, our mean scores of the total adherence behavior and its sub-domains were all higher than those reported by Arad et al [ 22 ] which reported a total adherence score of 513.6 compared to 919.8 in our study. Furthermore, non-adherence behaviors among ESRD patients showed wide variations in the literature ranging from 2% to 80.4% for dietary restrictions, 9.7%–75.3% for fluid restrictions, 15.4%–99% for medical prescriptions, and to HD attendance as 33.6%.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study it was determined that the prevalence of IDH significantly decreased after patient education and cooling of the dialysate (Figure 1). This is in line with Arad et al, (2021) Besides patient education for reducing IDH, another important intervention in this study is dialysis fluid cooling. In a meta-analysis conducted on this subject, it was determined that low-temperature dialysates reduced the rate of IDH development by 70% (Mustafa et al, 2016;Rad et al, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…In this way, satisfaction, quality of life, and independence are increased. Besides complications, anxiety, and cost are reduced (Arad et al, 2021). Nephrological nurses play a critical role in preventing and managing IDH.…”
Section: Introductionmentioning
confidence: 99%
“…It implied that the nursing method combined with TTM of behavior change can relieve patients' bad psychological state, increase the compliance to fluid intake and also effectively reduce the incidence rate of dialysis-associated acute complications. Starting from the point that research objects show some behaviors unfavorable for the treatment, TTM of behavior change aims to guide the research objects to change their bad behaviors, take intervention measures by stage, and strengthen new beneficial behaviors until the objective of health behaviors is realized [24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%